Food and water security under global change: Developing adaptive capacity with a focus on rural Africa - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2010)
Food and Water Security under Global Change: Developing Adaptive Capacity with a Focus on Rural Africa The project “Food and Water Security under Global Change: Developing Adaptive Capacity with a Focus on Rural Africa” aimed to provide farmers, policymakers, and other stakeholders in Ethiopia and South Africa with tools to make better adaptive decisions in the face of climate-related risk. The project combined household surveys and stakeholder forums, which examined local perceptions of the long-term effects of global warming and adaptive responses, with climate change impact analysis. The results of the study showed that vulnerability to climate change is dependent on a number of factors including the degree to which farmers are exposed to climate change, their sensitivity to climate changes, and their adaptive capacity. Given that the nature of vulnerability will vary depending on these factors and given large spatial differences across regions, policymakers should tailor strategies to reduce vulnerability to local conditions. An effective way to address the impacts of climate change would be to integrate adaptation measures into sustainable development strategies, thereby reducing the pressure on natural resources, improving environmental risk management, and increasing the social wellbeing of the poor. Moreover, early warning of extreme climatic events, such as droughts and floods, can alert farmers to the shocks, enabling them to take action to reduce their vulnerability, such as selling livestock and increasing food stocks. The findings indicate that adaptation strategies need to go beyond improved water storage, additional irrigation, and new crop varieties to include a focus on improving farmers’ access to information, credit, and markets. Information on climate changes and appropriate adaptation responses is critical to ensure that farmers are able to make the necessary adjustments to their farming practices. To ensure that the right information gets to the right people, proactive investments, policies, and extension services must explicitly target those who are most vulnerable to climate change: subsistence farmers, women, children, and marginalized or less-educated groups. Additional investments of US$2 billion per year in public agricultural R&D, rural roads, female secondary education, irrigation, and access to clean water could significantly reduce the adverse effects of climate change in Sub-Saharan Africa. US$5 billion per year could help reduce the number of malnourished children to one-third of its current level over the next fifty years.